Productive performance of crossbred Holstein x Jersey cows compared to Holstein straightbred cows - Thaler Neto, André; Rodrigues, Rafael Sachet; Córdova, Helder de Arruda (Revista de Ciências Agroveterinárias, 2013)
Milk production in temperate and subtropical climates is mostly based on pure bred cows. Changes in the value of milk composition of the marketed milk, as well as research efforts in countries with highly developed dairy farming with the use of crossbreeding between specialized dairy breeds, has made the practice of crossbreeding of Holstein and Jersey breeds more popular in southern Brazil. The objective of this study was to compare production of crossbred Holstein x Jersey compared to purebred Holstein. The assessments were carried out from data collected in three dairy farms in the states of Santa Catarina and Paraná. Crossbred Holstein x Jersey cows had lower milk yield in a 305 day lactation period (p<0.01) compared to pure bred Holstein cows (9509.7 vs. 8966.0 kg), which represents 94% of the milk produced by pure bred cows. However, crossbred Holstein x Jersey cows had higher levels of fat (2.63 vs. 2.35%) and protein (3.10 vs. 2.97%) in milk and produced more fat in 305 days of lactation (242.6 vs. 227.0 kg) (p<0.01). The estimated performance values for crossbred Holstein x Jersey cows compared to the Holstein straightbred cows can help producers in the decision about the use of pure bred cows or the introduction of a crossbreeding program in dairy farms.